Promoting Students’ Reading Proficiency through Reciprocal Technique - Farid Noor Romadlon (Vision: Journal for Language and Foreign Language Learning, 2017)
Teaching English in High School level (Junior High School and Senior High School) is more exposed in reading and writing skills for the target of final examination (UN).Consequently, students need to sharpen their reading and writing ability. It also must be done by students in a non-formal Senior High School known as KejarPaket C without any exception. Improving reading skill can be done through doing more reading activities in various types of text. This activity will add students’ vocabularies and their knowledge about more topics of the texts. Besides, the way teachers deliver the material deals with techniques, methods, or strategies also contributes in students’ progress of reading skill. Seeing the background of students in KejarPaket C who have various backgrounds and mostly are from low economic level or less motivated students for studying, teachers should concern more in exposing the material through the appropriate and effective technique. Carter (2001) brings an idea about a technique which teacher and students are taking place in dialogue and it resulted in students learning how to construct meaning when they are placed in must-read situations (tests or assignments). This was experimental research which was conducted to find the difference of students’ reading proficiency taught by using a technique called Reciprocal. The study found that the technique contributed significantly in improving students’ reading proficiency after they were taught by using Reciprocal. In brief, Reciprocal technique is an effective way to improve students’ reading proficiency.